SURVEY OF PULMONARY TUBERCULOSIS BASED ON SYMPTOMS AND SPUTUM EXAMINATION IN CHIKKAMAGALURU - GY, DAYANANDA; E, CHANDRAKALA; HC, SUPRIYA (Innovare Journal Health Sciences, 2020)
Objectives: Tuberculosis (TB) is the most common problem in the world. This study was aimed to assess the gender, age, and occupation prevalence rate of TB infection in Chikkamagaluru, Karnataka, India. Methods: The survey was carried out in Chikkamagaluru from January to May 2012. The data were collected by direct interview of the patients with the help of medical officers. Then, the data were assessed and categorized based on gender, age, and occupation. Results: A total of 97 pulmonary TB patients were identified, among them, males are more (74.22%) prone to TB than that of females (25.72%). This may be because males are more exposed to smoking, drinking, etc. The data were also scrutinized for age-wise distribution of pulmonary TB, and it was found that patients in the age group of 41–50 years are more affected than the other age group, and pulmonary TB was more prominent than extrapulmonary TB. The Mycobacterium tuberculae patients grading are more in 3+ than in 2+ and 1+ grading type of TB affected individuals. Conclusion: This study concludes that males are more to TB due to abuse of alcohol, smoking, and occupation-wise laborers which are more infected.